Real experiences and care needs of frail older patients: a systematic review of qualitative studies - Peng, Shuo; He, Hongzhi; Luo, Xi; Kang, Jingping; Wang, Xinyi; Tan, Yongqiong (Frontiers in Public Health, 2025)
ObjectiveBy conducting a meta-synthesis of qualitative research, this study evaluates the real experiences and care needs of frail older patients, providing valuable references and insights for care service providers, policymakers, and medical researchers in developing intervention programs.DesignPubMed, Web of Science, Scopus, Embase, CINAHL, and PsycINFO were searched from the establishment of the databases to August 25, 2024.SettingThe real experiences and care needs of frail older patients are gradually becoming the focus of social attention. Qualitative research is of great significance for improving the quality of care services for such patients in the future.Outcome measuresThe quality of the studies included was appraised using the Joanna Briggs Institute Quality Assessment of Qualitative Research criteria. Data extraction was performed using NVivo (v14), and results were synthesized using a meta-synthesis approach.Results511 frail older patients were included in 15 studies. Three main themes were identified: the negative impact of frailty on the physical, psychological, and behavioral aspects of older patients; positive attitudes toward the current situation among frail older patients; and the multidimensional care needs of frail older patients.ConclusionFrail older adults face multidimensional challenges in physiology, psychology, and behavior, and have care needs in areas such as professional services and social support.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251038626.